A survey on office designs of general practitioners in Manila - Gomez, Susan S.
In this paper, it is the main purpose to study the design of the dental office of general practitioners in Manila with the objectives to determine whether they conform to the idea of an adequate dental office, to determine whether the floor plans or the arrangements in the offices allow efficient traffic flow patterns within individual spaces and between the various spaces and to determine the most common overall office layout. A questionnaire consisting of three parts was used in gathering information. As a result from the various tests for the different surveys, it is concluded that general practitioners in Manila do not conform to the idea of an adequate dental office.